The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acsaem.1c03845
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis and Screening of a Ternary NiFeCoOx Library for the Oxygen Evolution Reaction

Abstract: The development of an efficient catalyst for the oxygen evolution reaction (OER) is critical to fulfilling the mission of hydrogen generation by water splitting. Various multicomponent systems have been investigated so far for the OER, although a systematic investigation is lacking and there are discrepancies as to which formulations make the best catalyst. Here, we perform a systematic investigation of a ternary Ni-Fe-Co oxide gradient library for the OER, using a combinatorial approach. This approach allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…10,[60][61][62] In our previous work, we have shown that the addition of modest amounts of cobalt to the NiFe system can have a significant impact on the OER activity. 29 Various such transition elements (Cr, Ce, V, Mn) owing to their tuneable d-band structure, have been incorporated into the standard NiFe system to improve its catalytic properties. [63][64][65][66][67] In the study of multimetal alloys, obtaining the same volume of data as we obtained and effectively spanning the same compositional space as achieved in our work would require a substantially higher number of experiments, time, and cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,[60][61][62] In our previous work, we have shown that the addition of modest amounts of cobalt to the NiFe system can have a significant impact on the OER activity. 29 Various such transition elements (Cr, Ce, V, Mn) owing to their tuneable d-band structure, have been incorporated into the standard NiFe system to improve its catalytic properties. [63][64][65][66][67] In the study of multimetal alloys, obtaining the same volume of data as we obtained and effectively spanning the same compositional space as achieved in our work would require a substantially higher number of experiments, time, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we demonstrated the incorporation of Fe and Co into a Ni matrix as an effective strategy to improve the catalytic performance. 29 Although cobalt improves the OER performance, cobalt is a critical raw material and its mining raises environmental, social, and governance issues. Herein, we chose vanadium as a suitable candidate to drive down the overpotential of the NiFe based catalysts relying on vanadium's multivalency, relative abundance, 30 and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale porosity in mixed metal phosphonates, such as Ni-W mixed metal phosphonate, has been found to be responsible for efficient photoelectrochemical OER in alkaline conditions, showcasing the versatility of these materials in harnessing solar energy for water splitting [97]. Furthermore, the combinatorial synthesis and screening of ternary NiFeCoO x libraries have provided insights into the optimization of mixed metal oxide combinations for the oxygen evolution reaction [98].…”
Section: Further Inorganic Materials For Water Splittingmentioning
confidence: 99%
“…8 Furthermore, it can be easily implemented as combinatorial deposition method for (1) thickness gradients by adjusting the covered area of multiple spray cycles [9][10][11][12][13][14][15] and (2) composition gradients a Energy Conversion and Hydrogen, Center for Energy, AIT Austrian Institute of by capitalizing the lateral spread of the spray cone and overlapping different precursor solutions consecutively 16 or simultanously. [17][18][19] Directly mixing multiple solutions during a laterally resolved coating process has already been reported. 20 In this contribution we synthesize combinatorial films with two-dimensional composition gradients of metal oxides.…”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, it can be easily implemented as combinatorial deposition method for (1) thickness gradients by adjusting the covered area of multiple spray cycles 9–15 and (2) composition gradients by capitalizing the lateral spread of the spray cone and overlapping different precursor solutions consecutively 16 or simultanously. 17–19 Directly mixing multiple solutions during a laterally resolved coating process has already been reported. 20…”
Section: Introductionmentioning
confidence: 99%